1996
DOI: 10.1007/bf00171058
|View full text |Cite
|
Sign up to set email alerts
|

The role of extraneuronal amine transport systems for the removal of extracellular catecholamines in the rabbit

Abstract: As selective inhibitors of the extraneuronal monoamine uptake system (uptake2) suitable for in-vivo studies were not available, the question of whether uptake2 plays a definite role in vivo is largely unresolved. We attempted to resolve the question by using 1,1'-diisopropyl-2,4'-cyanine iodide (disprocynium24), a novel agent that blocks uptake2 in vitro with high potency. Anaesthetized rabbits were infused with 3H-labelled noradrenaline, adrenaline and dopamine, and catecholamine plasma clearances as well as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
17
0

Year Published

1996
1996
2009
2009

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 42 publications
2
17
0
Order By: Relevance
“…1 B, C) revealed that the two drugs have similar pharmacokinetics characterized by short elimination halfqives (<10 rain) and very high plasma clearances (>150 ml kg -1 minq). The high plasma clearance of disprocynium24 obtained here from the AUC after a bolus injection (180 ml kg -1 min -1) was confirmed by Friedgen et al (1996) who found a value of 146 ml kg 1 rain q based on constant-rate infusions of the drug. The high plasma clearances of both drugs were in part due to drug accumulation in blood cells.…”
Section: Discussionsupporting
confidence: 53%
“…1 B, C) revealed that the two drugs have similar pharmacokinetics characterized by short elimination halfqives (<10 rain) and very high plasma clearances (>150 ml kg -1 minq). The high plasma clearance of disprocynium24 obtained here from the AUC after a bolus injection (180 ml kg -1 min -1) was confirmed by Friedgen et al (1996) who found a value of 146 ml kg 1 rain q based on constant-rate infusions of the drug. The high plasma clearances of both drugs were in part due to drug accumulation in blood cells.…”
Section: Discussionsupporting
confidence: 53%
“…Uptake 2 is a sodium-and chloride-independent, low-affinity, high-capacity transport system initially described in heart, smooth muscle, and glandular cells (Iversen, 1965). Contrary to sodium-driven, high-affinity neuronal Uptake 1 , Uptake 2 can be inhibited by corticosteroids and O-methylated catecholamines as well as cyanin-related compounds (Trendelenburg, 1988;Friedgen et al, 1996;Wu et al, 1998). The main OCT subtypes (OCT1, OCT2, and OCT3) isolated these last few years in humans and rodents display pharmacological profiles that match these general characteristics (Grundemann et al, 1997(Grundemann et al, , 1998aBusch et al, 1998;Wu et al, 1998;Hayer-Zillgen et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…The cyanine derivative disprocynium 24 (D24) was isolated as a highly potent uptake-2 inhibitor in vitro (23). However, the application of D24 in vivo to study uptake-2 was revealed to be limited, as it was shown previously that D24 blocks not only uptake-2 but also other transport mechanisms that clear catecholamines (8,11).…”
mentioning
confidence: 99%